Predicting the drivers of Bothrops snakebite incidence across Brazil: a spatial analysis - Barbosa da Silva, Franciely Fernanda (2024)
Snakebite envenoming poses a significant public health challenge on a global basis, affecting millions of people annually and leading to complications that may result in fatalities. Brazil stands as one of the countries most impacted by snakebite envenoming, with snakes of the Bothrops genus being responsible for most bites. The current study aimed to identify the determinants of Bothrops snakebite incidence across different regions of Brazil. An ecological study was conducted using municipality-aggregated data, with snakebite incidence as the dependent variable. The study period comprised the years 2015–2021. We constructed Species Distribution Models (SDMs) for Bothrops species, and information was collected on precipitation, runoff, maximum and minimum temperatures, native forest, historical forest loss, agriculture, and pasture in each Brazilian municipality. These data were employed to assess the association between snakebite incidence and biotic, climatic, and landscape factors. The data were analyzed using Generalized Least Squares (GLS) regression. The SDMs demonstrated good performance. The average annual snakebite incidence during the study period ranged from zero to 428.89 per 100,000 inhabitants, depending on the municipality. Higher incidence rates were concentrated primarily in municipalities in the northern region of the country. In this study, we found that nationwide, areas with extensive native forests and those that have historically experienced significant loss of forest cover exhibited higher snakebite incidence rates. Additionally, areas with higher temperatures and precipitation levels, as well as greater climatic suitability for the species B. jararaca, showed significantly higher snakebite incidence rates in the South and Southeast of Brazil, respectively. These associations may be linked to increased snake abundance and active behavior, as well as to engagement in activities favoring human-snake contact in these areas. The findings of this study can contribute to the improvement of prevention and control strategies for this public health issue in Brazil.